The influence of festivals and events on tourists’ willingness to visit Madeira island - Vieira, É.; Dias, Á.; Patuleia, M. (Geojournal of Tourism and Geosites, 2026)
The present study aims to understand the impact of summer festivals and events in willingness to visit Madeira Island. Based on the theory of planned behavior and willingness to participate in festivals and events, it analyses the correlation of these factors in willingness to visit. Moreover, age is used as a moderator effect in willingness to participate to conclude the final impact in the intention to travel to this Island. After conducting a survey and analyzing the data collected, a new understanding on the theory of planned behavior in the tourism market was achieved. In this context, the social environment around the individual has proved to not influence the decision to visit the hosting destination. Additionally, the willingness to participate in summer festivals and events is found to be a factor motivating and directly affecting the decision to visit Madeira Island. Age plays a role in this decision, influencing the intention to attend specific types of events. Therefore, it moderates, consequently, the main object in this study. These findings are crucial to the tourism market since it enables a new strategic view that can be explored and used worldwide to attract more people to a destination. Festivals and events are a growing market, beginning to be conceptualized as a tourism product. Therefore, this study contributes to existing literature by exploring this phenomenon that attracts tourists and leverages regions. Furthermore, it supports the theory of planned behavior in the tourism context, providing new findings and developments.